Evaluation of quantitative biomarkers of aging in human PBMCs - Owen, Brady M.; Phie, James; Huynh, Jennifer; Needham, Scott; Fraser, Cameron (Frontiers in Aging, 2023)
Functional decline with age contributes significantly to the burden of disease in developed countries. There is growing interest in the development of therapeutic interventions which slow or even reverse aging. Time and cost constraints prohibit the testing of a large number of interventions for health and lifespan extension in model organisms. Cell-based models of aging could enable high throughput testing of potential interventions. Despite extensive reports in the literature of cell properties that correlate with donor age, few are robustly observed across different laboratories. This casts doubt on the extent that aging signatures are captured in cultured cells. We tested molecular changes previously reported to correlate with donor age in peripheral blood mononuclear cells (PBMCs) and evaluated their suitability for inclusion in a panel of functional aging measures. The tested measures spanned several pathways implicated in aging including epigenetic changes, apoptosis, proteostasis, and intracellular communication. Surprisingly, only two markers correlated with donor age. DNA methylation age accurately predicted donor age confirming this is a robust aging biomarker. Additionally, the apoptotic marker CD95 correlated with donor age but only within subsets of PBMCs. To demonstrate cellular rejuvenation in response to a treatment will require integration of multiple read-outs of cell function. However, building a panel of measures to detect aging in cells is challenging and further research is needed to identify robust predictors of age in humans.